2011
DOI: 10.1111/j.1463-5224.2011.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of retinal vessels in the optic disk in a Göttingen minipig experimental glaucoma model

Abstract: The changes in the glaucomatous optic disk of the minipig imply a predominant involvement of the arterioles. However, in humans with primary open-angle glaucoma (POAG), both the arterioles and the venules are displaced, and the central excavation is easier to distinguish, because of the absence of a central venous ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…In an attempt to reduce the use of nonhuman primates, we increasingly consider Göttingen minipigs for regulatory toxicology studies, including investigation of ocular drug delivery routes. In addition, the minipig is an interesting species in ocular research translatable to human disease conditions, such as glaucoma (Dan et al 2008;Galdos et al 2012;Ruiz-Ederra et al 2005), retinitis pigmentosa (Ross et al 2012), proliferative vitreoretinopathy (Umazume et al 2012), choroidal neovascularization (CNV; Kiilgaard et al 2005;Lassota et al 2008), retinal degeneration (Huang et al 2000) or detachment (Iandiev et al 2006), in transplantation studies (Klassen et al 2008), and as a model for selective retinal capillary closure in diabetic retinopathy (Foulds et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to reduce the use of nonhuman primates, we increasingly consider Göttingen minipigs for regulatory toxicology studies, including investigation of ocular drug delivery routes. In addition, the minipig is an interesting species in ocular research translatable to human disease conditions, such as glaucoma (Dan et al 2008;Galdos et al 2012;Ruiz-Ederra et al 2005), retinitis pigmentosa (Ross et al 2012), proliferative vitreoretinopathy (Umazume et al 2012), choroidal neovascularization (CNV; Kiilgaard et al 2005;Lassota et al 2008), retinal degeneration (Huang et al 2000) or detachment (Iandiev et al 2006), in transplantation studies (Klassen et al 2008), and as a model for selective retinal capillary closure in diabetic retinopathy (Foulds et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, ocular fluorescent dye angiography (Galdos et al 2012) and high-quality SDOCT have been established (McLellan and Rasmussen 2012;Rosolen et al 2012). In addition, there is increasing knowledge about the correlation of in vivo OCT scan results with histopathology of the porcine eye (Fatehee et al 2011;Gloesmann et al 2003;Huang et al 2000;Rosolen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of the eight animals that underwent episcleral vein cauterization, 57,1% presented statistically significant differences (p<0.05) of IOP, when comparing the experimental left eyes (LE) and the control right eyes (RE), indicating that these animals had glaucoma [23]. IOP values of control eyes averaged 22.43 ± 4.46 mmHg and glaucomatous eyes averaged 26.04 ± 5.01 mmHg (p<0.01, Figure 1 and Table 1).…”
Section: Iop Measurementsmentioning
confidence: 93%
“…Recently,Galdos et al [23]. studied in the Göttingen minipigs experimental glaucoma model the changes in the vasculature of the optic disk demonstrating that they were similar to those observed in human POAG In previous studies Ruiz-Ederra et al [24] demonstrated that moderated increase of IOP in pig eyes, caused by cauterization of the episcleral veins, induced retinal ganglion cell death following a pattern similar to that described in humans.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation